MAIN TECHNOLOGICAL INDICATORS OF SORGHUM FLOUR (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article presents the results of a study conducted to examine the main factors representing the technological indicators of sorghum flour grown in the northern regions of Uzbekistan, and makes scientifically based conclusions.